2009
DOI: 10.1055/s-0028-1082303
|View full text |Cite
|
Sign up to set email alerts
|

Integrierte Tinnitusintensivbehandlung: Verringerung der tinnitusbedingten Belastung während einer 1-Jahres-Katamnese

Abstract: The outpatient intensive multidisciplinary tinnitus therapy with long-term aftercare has proved to be an effective method in the treatment of patients with chronic tinnitus. The outpatient setting enables the instant implementation of strategies learned during therapy in the patients' everyday life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…Our results regarding reduction of depressive symptoms support prior studies stating that the reduction of depressive symptoms is an often found outcome in the treatment of tinnitus (22,23). In summary, our results support earlier studies (15,18,19,22,24,25) that a treatment specifically geared at tinnitus in addition to psychiatric treatment as usual benefits people suffering from tinnitus.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results regarding reduction of depressive symptoms support prior studies stating that the reduction of depressive symptoms is an often found outcome in the treatment of tinnitus (22,23). In summary, our results support earlier studies (15,18,19,22,24,25) that a treatment specifically geared at tinnitus in addition to psychiatric treatment as usual benefits people suffering from tinnitus.…”
Section: Discussionsupporting
confidence: 91%
“…All included outcome measures, such as the BDI-II to assess depressive symptoms, showed a significant difference between the values at baseline compared to the assessment before discharge from the clinic. The analysis of the subjective symptom intensity as measured by the BSI also demonstrated a clear reduction throughout the course of treatment, which confirms prior findings (15,18,21,24,25). Our results regarding reduction of depressive symptoms support prior studies stating that the reduction of depressive symptoms is an often found outcome in the treatment of tinnitus (22,23).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Tinnitus is considered to be at a decompensated level (permanent annoyance and psychological strain) with a TQ score of 47 points or higher (grade 3 and 4) and to be at a compensated level (low secondary symptoms) at 46 points or lower (grade 1 and 2) (Lenarz, 1992; Goebel and Hiller, 1998; Stobik et al, 2005; Mazurek et al, 2009). Therefore, we defined a clinically relevant change as a change from a decompensated to a compensated level, i.e., below 47 points.…”
Section: Methodsmentioning
confidence: 99%